How is student scientific attitude profile toward chemistry learning with research-oriented collaborative inquiry learning? - Yuyum Fahmidani; Eli Rohaeti (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
This study aims to describe the profile of scientific attitudes of XI grade high school students in Sleman who learned with the Research-Oriented Collaborative Inquiry Learning REORCILEA. The sample in this research was 30 high school students who were selected using a purposive sampling technique. REORCILEA is an integrated learning model between research-based, inquiry, and collaborative learning. The research was descriptive qualitative designed, and the results of the descriptive analysis revealed that high school students who taught with REORCILEA had a 10% good, 86, 67 % enough, and 3.33 % low scientific attitude profile. Scientific attitude toward chemistry learning profile assessed with a questionnaire developed by the researcher. Students' scientific attitudes are described by seven aspects of scientific attitude, specifically curiosity, rational thinking, openmindedness, concern with evidence, and honest acting according to the rules.